Contactless Energy Supply for Medical Drill with Integrated Temperature Sensor - Knott Anna-Lena; Sanders Mark; Prinzen Tom; Klenzner Thomas; Schipper Jörg; Kristin Julia; Schmitt Robert H. (Current Directions in Biomedical Engineering)
An atraumatic approach to the inner ear is an important goal in the future development of cochlear implant surgery, as the current surgical procedure for electrode insertion is highly invasive. To reduce invasiveness, minimally invasive surgical options are being explored, such as the insertion of one or more drill channels. Due to the proximity to critical structures, a temperature sensor is incorporated into the medical drill for process parallel temperature monitoring to prevent thermal damage. The temperature data is sent to the analysis hardware via Bluetooth BLE. This requires a power supply for the electronics on the drill. There are a number of limitations to the design of such a power supply. For one, the drill is rotating. Therefore, the energy generation must be contactless. Secondly, the energy generation should not depend on the rotation of the drill, so that the temperature can be measured even without the drill rotating and the rotational speed of the drill is not limited. In this paper, we propose a solution for a contactless energy transmission system (ETS) based on inductive coupling. Considering the dimensional limitations of attaching the electronics to the drill shaft, a multilayer PCB coil with multiple contacts for different number of turns is developed. The electrical circuit is simulated and the best settings are identified. The power supply is validated according to the predefined requirements. In the future, the medical drill will be built with the newly developed ETS. Sterilization and wear tests are performed to confirm the suitability of the drill with integrated temperature sensor for the operating room.